A Comparative Study Between Femoral Nerve Block and Suprainguinal Fascia Iliaca Compartment Block for Post-Operative Analgesia in Femur Fracture Fixation - Regmi, Nabin Kumar; Gurung, Sandeep; Sagar DC, Gopal; Kharel, Subina (Journal of Nepalgunj Medical College, 2024)
Introduction: Femur fractures and their surgical fixations are common. Adequate postoperative pain relief is mandatory as it facilitates rapid recovery by enhancing early ambulation and mitigating stress response. This is barely achievable with conventional pain control methods. Ultrasound-guided regional blocks like femoral nerve block and supra-inguinal fascia iliaca compartment block are simple yet promising techniques for postoperative analgesia in femur fractures. Aims: To compare post-operative analgesia duration and satisfaction attained between the patients receiving ultrasound-guided femoral nerve block with, those receiving ultrasound-guided supra-inguinal fascia iliaca compartment block, after femur fracture fixation. Methods: Seventy-four patients, aged 16−85 years, of either sex, ASA I−II, who underwent femur fracture surgical fixations under spinal anesthesia, were randomly divided into two equal groups: groups 1 and group 2. Postoperatively, Group 1 (n= 37) received a femoral nerve block with 15 ml 2.5% bupivacaine whereas Group 2 (n = 37) received a supra-inguinal fascia iliaca compartment block with 30 ml 2.5% bupivacaine. Duration of analgesia, patients' level of satisfaction, visual analogue scale scores, and hemodynamic parameters at different time intervals were recorded in the first 24 hours postoperatively and compared. Results: The demographic profiles between the two groups were comparable. Group 2 had a significantly longer duration of analgesia than Group 1, with the means 795.14 vs 538.65 minutes respectively, and a P value of .002. Although group 1 patients had predominantly 3 and 4 levels of satisfaction whereas group 2 had 4 and 5, there was no statistically significant difference in patients’ level of satisfaction between the groups (P=.249). Conclusion: Supra-inguinal fascia iliaca block provides a longer duration of analgesia than femoral nerve block in femur fracture fixation. The level of satisfaction in both groups is high and comparable.